An Estimated Model with Macrofinancial Linkages for India - Saxegaard, Magnus (IMF Working Papers; Working Paper ;, 2010)
This paper develops a small open economy dynamic stochastic general-equilibrium model with macrofinancial linkages. The model includes a financial accelerator--entrepreneurs are assumed to partially finance investment using domestic and foreign currency debt--to assess the importance of financial frictions in the amplification and propagation of the effects of transitory shocks. We use Bayesian estimation techniques to estimate the model using India data. The model is used to assess the importance of the financial accelerator in India and the optimality of monetary policy.